Inversion of Reservoir Parameters for Oil Extraction Based on Deformation Monitoring With InSAR - Yue Ma; Lu Zhang; Ding Chen; Haolei Zhang; Yitong Zheng; Shiyong Yan (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Frequent water injection and oil extraction can potentially lead to changes in reservoir pressure, burst or collapse of casings, and corresponding variations on the ground surface. Attention should be focused on developing the strategies to monitor and mitigate the adverse consequences of oilfield operations. Here, the distributed scatterer InSAR (DS-InSAR) technique is applied to estimate the surface deformation of Daqing oil field with the surveillance period from 2015 to 2019. Furthermore, Bayesian method with three models, including Mogi, prolate spheroid, and Okada, are implemented to obtain parameters related to underground cavities, using cumulative deformation recorded between June and December 2015 and May and December 2016 as input. Inversion validation measurements were carried out by comparing the results with field data in the area of interest. Our findings demonstrate that, in comparison to other models, the prolate spheroid could recover both reservoir pressure and surface deformation, offering compelling evidence in favor of mitigating shear failure-related issues. A dual-source prolate spheroid model is also used to simulate large-scale deformation on the surface of oilfield. Its characteristics are nearly in line with variations in reservoir pressure and casing depth, which may minimize the negative consequences of casing failures and guarantee the stability of oil production.